Genotype-specific rhizosphere microbiome assembly and its impact on soybean (Glycine max (L.) Merri.) yield traits - Han, Xiaodong; Zhang, Xiaomin; Su, Minli; Yang, Shuqian; Feng, Shilin; Tian, Tian; Chen, NarenTuya; Zhao, Guofen; Huang, Lichun; Wang, Guihua (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe rhizosphere microbiome plays a critical role in plant growth and productivity. However, the genotype-specific dynamics and functional influence of these microbial communities on soybean (Glycine max (L.) Merri.) yield traits remain underexplored. This study investigated the composition and functional implications of rhizosphere microbial communities in conventional and genetically modified (GM) soybean varieties under field conditions.MethodsA comparative analysis was conducted on rhizosphere microbial communities associated with conventional H0269 and transgenic Z1510 and M579 soybean varieties at seedling and flowering stages. High-throughput sequencing of 16S rDNA and ITS regions was used to profile bacterial and fungal communities. Alpha and beta diversity metrics were assessed, and correlation analyses were performed to identify microbial taxa linked to yield traits.ResultsDistinct microbial community structures were observed across soybean genotypes and growth stages. Proteobacteria, Acidobacteriota, and Actinobacteria were dominant bacterial phyla, while Ascomycota predominated among fungi. Genotype-specific differences were evident, with M579 exhibiting the highest bacterial alpha diversity. Beta diversity analysis revealed significant shifts in microbial composition between growth stages, particularly for bacterial communities. Correlation analysis identified 15 bacterial and 13 fungal species significantly associated with yield traits such as plant density, grain weight, and theoretical yield.DiscussionThe results highlight genotype-dependent recruitment of rhizosphere microorganisms and their potential impact on soybean productivity. GM soybean varieties selectively enriched beneficial microbes that may enhance nutrient uptake, stress tolerance, and disease resistance. These findings provide valuable insights into plant-microbe interactions, paving the way for developing microbial inoculants and breeding strategies to optimize soybean yield in sustainable agriculture.